(untitled) (International Journal of Studies in Nursing, 2020)
Background: Depression is the “common cold” of psychiatry. Purpose: The purpose of this review was to discuss a variety of topics involved with this disease process, including pathophysiology, the standard of practice, pharmacological treatments, clinical guidelines, and costs of the disease. Method: A thorough survey of the literature on “understanding depression” was implemented for this study. Findings: Best practices, including plan implementation and evaluation, are discussed. The cost of depression is more extensive than financial costs, though research concludes that the more severe depressive symptoms present, the cost of care is reflected as higher. Through the hypothetical plan suggested, there would be an increased adherence to the Standard of Practice Guidelines to increase screening for depression at the outpatient mental health clinic at the author’s healthcare facility.